Impact of mothers' distress and emotional eating on calories served to themselves and their young children: An experimental study. Issue 6 (5th January 2022) - Warnick, Jennifer; Cardel, Michelle; Jones, Laura; Gonzalez‐Louis, Rachel; Janicke, David
Summary: Background: Parents play a significant role in children's eating behaviours and food environment. Emotional eating (i.e., eating due to/to cope with emotions regardless of hunger) can contribute to excess energy consumption and subsequent weight gain. Yet, there is a paucity of research examining mothers' feeding and eating behaviours in the presence of their young children during times of acute distress. Objective: The current study examined whether manipulated maternal mood impacted subsequent eating and parental‐feeding in mothers with overweight or obesity with their preschool aged children in a laboratory‐based experiment. Methods: Mothers ( n  = 47) with overweight or obesity and their preschool aged children were randomized to either an acute distress or control group. After completing a task which manipulated mothers' moods, respectively, dyads were offered a buffet of snack foods. Measures of mothers' reported emotional eating and distress were collected, and calories served and consumed were objectively measured. Results: There were no between‐group differences regarding calories served or consumed. Mothers across both groups who reported higher emotional eating served themselves ( p  = 0.014) and their children ( p  = 0.007) less food, and mothers consumed less food ( p  = 0.045). Mothers who reported higher emotional eating and increased acute distress fed their children less food ( p  = 0.02) and both children and mothers ate less food ( p  < 0.05). Conclusions: Results suggest that mothers who report emotional eating tendencies may feed their children less food during periods of acute distress.